“JIRAB AL-MAMNUN”: DISCUSSING THE WORK AND ITS AUTHOR - Gusejnov, Abdusalam Abdulkerimovic (History, Archeology and Ethnography of the Caucasus, 2024)
In light of the preparation of the Russian translation of Gasan Alkadari’s book “Jirab al-Mamnun”, this article examines its role in the spiritual development of Dagestan. The author proceeds from the accepted scientific characterization of Alkadari as an educator and considers this book as an example of his educational activity. Drawing on the classical European concept of education, the article reveals the uniqueness of its Dagestani version, characterized by a collective search for rational solutions to emerging life challenges. This approach, conducted through a free epistolary form, aimed to combine religious worldviews with the contemporary scientific and technological achievements. In this context, both the inquirer’s persona and the inquiry itself are integral to the holistic structure of the Enlightenment era, as are the respondent’s identity and their capacity to answer. The transition from a state of illiteracy and dark prejudices to independent thinking and mastery of written literacy and scientific knowledge, although marked by outstanding philosophers-enlighteners, is depicted as a collective endeavor. The article substantiates this central idea through several stages of analysis: basic characteristics of the concept of enlightenment as a historical era, emphasizing the dominance of rational worldviews and morally responsible human behavior; the beginning of Dagestan’s Enlightenment as a continuation of the unifying mission of the Imam Shamil’s movement; “Jirab al-Mamnun” as a unique form of societal self-awareness and its genre-specific nature; enlightenment as a joint quest for truth; the art of asking; the art of answering; epistolary character as a specific form of connecting those who know and those who do not know, and the affirmation of science as a common good.